Trading Animal Lives: Ten Tricky Issues on the Road to Protecting Commodified Wild Animals. (14th April 2021) - Macdonald, David W; Harrington, Lauren A; Moorhouse, Tom P; D'Cruze, Neil
Abstract: Wildlife commodification can generate benefits for biodiversity conservation, but it also has negative impacts; overexploitation of wildlife is currently one of the biggest drivers of vertebrate extinction risk. In the present article, we highlight 10 issues that in our experience impede sustainable and humane wildlife trade. Given humanity's increasing demands on the natural world we question whether many aspects of wildlife trade can be compatible with appropriate standards for biodiversity conservation and animal welfare, and suggest that too many elements of wildlife trade as it currently stands are not sustainable for wildlife or for the livelihoods that it supports. We suggest that the onus should be on traders to demonstrate that wildlife use is sustainable, humane, and safe (with respect to disease and invasion risk), rather than on conservationists to demonstrate it is not, that there is a need for a broad acceptance of responsibility and, ultimately, widespread behavior change. We urge conservationists, practitioners, and others to take bold, progressive steps to reach consensus and action.